Prevalence of burnout and its associated factors among healthcare providers in government health clinic in Kuantan, Pahang during covid-19 pandemic - Tg Arif @ Tg Zainuddin, Tg Putri Syarizan; Said, Abdul Hadi; Yusof, Muhammad Zubir (2021)
Introduction: Burnout is defined as a psychological syndrome of emotional exhaustion, depersonalization, and reduced personal accomplishment that can occur among individuals who work with other people in some capacity, especially in demanding job like healthcare professionals. High level of burnout in healthcare providers has been associated with decreased work efficiency. The aim of this study was to identify the extent of burnout among them and to identify its associated factors. Materials and Methods: In this cross-sectional study, healthcare providers consist of doctors, nurses, medical assistants and pharmacists in government health clinics in Kuantan, Pahang were studied. Oldenburg Burnout Inventory was used for this study which consists of 16 questions. Results: A total of 308 respondents were included. Mean age was 37.14 years, and 85.4% were females. Malay constituted 96.8% while Chinese and Indian, 2.3% and 1.0% respectively. Among them, 54.9% were nurses, 23.4% were doctors, 12.7% were medical assistants and 9.1% were pharmacists. This study revealed 55.8% of the respondents had high burnout. There is a significant association between high burnout and perception of underpaid with the p-value of 0.010. Conclusion: The prevalence of burnout among healthcare providers in this study is lower compared with the previous studies. However, it is not a negligible number for us. Ameliorating burnout among them should be a key priority for a sustainable care of the patients during the pandemic